GOOD CORPORATE GOVERNANCE DAN TINGKAT PAJAK EFEKTIF (Students' Journal of Accounting and Banking, 2013)
This study aims to examine the influence of good corporate governance to the effective tax rate to the agency theory perspective. The effective tax rate is one measure of tax planning. Tax planning will be done for enterprises will lead to the emergence of the agency problem. This agency problem is minimized by using a system of good corporate governance. Good corporate governance in this study is divided into five variables: the number of board of directors, the number of commissioners, the board independence, board stock company and majority shareholder. This study sampled using a purposive sampling and obtain data for 165 samples. This study is free from the normality test and the classical assumption test. These results indicate that the number of board of directors and management of the company stock has a positive and significant impact on the effective tax rate. The number of commissioners and the board independence has a positive and not significant impact on the effective tax rate. The latest results show that the majority shareholder has negative and significant impact on the effective tax rate. Keywords: corporate governance, the number of board of directors, the number of commissioners, the board independence, board stock companies, the majority shareholder, and the effective tax rate.